2004
DOI: 10.1183/09031936.04.00121203
|View full text |Cite
|
Sign up to set email alerts
|

Manganese superoxide dismutase is increased in the airways of smokers' lungs

Abstract: Oxidant stress is a key mechanism for smoking-induced chronic obstructive pulmonary disease (COPD). Smoking has been shown to upregulate several antioxidant enzymes, with potential effects on the prevention of the disease and/or its progression. Superoxide dismutases (SOD)s are the only enzymes capable of consuming superoxide radicals. The purpose of the present study was to investigate SODs in the lungs of nonsmokers, smokers and COPD patients.Manganese superoxide dismutase (MnSOD), copper zinc SOD (CuZnSOD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…However, we found a dramatic increase in SOD and CAT activities among patients with more severe COPD. It was found that erythrocyte SOD and CAT activities gradually increased from GOLD stages I to IV in COPD patients, which is supported by previous reports [36][37][38][39][40][41]. Indeed, various studies [40][41][42] except one study [7] have suggested that certain markers of oxidative stress may be related to tobacco smoking or to the severity of COPD.…”
Section: Discussionsupporting
confidence: 76%
“…However, we found a dramatic increase in SOD and CAT activities among patients with more severe COPD. It was found that erythrocyte SOD and CAT activities gradually increased from GOLD stages I to IV in COPD patients, which is supported by previous reports [36][37][38][39][40][41]. Indeed, various studies [40][41][42] except one study [7] have suggested that certain markers of oxidative stress may be related to tobacco smoking or to the severity of COPD.…”
Section: Discussionsupporting
confidence: 76%
“…Rangasamy et al (98) also reported an upregulation of a variety of antioxidant enzymes after mice were exposed to cigarette smoke. Interestingly, Harju et al (46) observed that the expression of superoxide dismutase (SOD) (an antioxidant enzyme) is higher in the central bronchial and alveolar epithelium of smokers with COPD than in that of nonsmokers, demonstrating the active involvement of antioxidants during oxidative stress.…”
Section: Role Of Reactive Oxygen Species In Copdmentioning
confidence: 99%
“…Altered levels of expression and activity of SODs in either lung or red blood cells were observed both in patients with COPD and in animals exposed to CS (10,15,22,42), whereas transgenic mice expressing SOD were reported to be resistant to elastase-or CS-induced pulmonary emphysema (12,44). However, the low affinity of SOD for tissues and low stability in plasma, with a half-life of a few minutes, are obstacles for its clinical use.…”
mentioning
confidence: 99%